The effects of inbreeding and laboratory-rearing on a pyraustid moth, Mimorista pulchellalis Dyar (Lepidoptera: pyraustidae), imported for the biological control of jointed cactus in South Africa - Wright, Margaret Dorothy (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1986)
Inbreeding was thought to be responsible for the loss in the second filial generation (F₂) of Amalafrida leithella Dyar, Cactoblastis mundelli Heinrich, Nanaia sp. Heinrich, Sigelgaita sp. Heinrich and Sigelgaita transilis Heinrich in the laboratory. This pre-empted the investigation of the effects of inbreeding on another cactophagous moth, Mimorista pulchellalis Dyar, an established biological control agent of jointed cactus in South Africa. Initially three populations were set up. A randomly-mating control (OUT 1) population, and a sibmating experimental (IN 1) population, consisted of laboratory-reared stock . A second experimental population (KR 1) comprised a small number of field-collected randomly-mating individuals which recreated the conditions under which the five abovementioned species were lost. The inbreeding depression of fifteen fitness components was assessed. The mean values of each component in each generation of treatments IN 1 and KR 1 were compared with those of OUT 1. In addition the mean values of IN 1 were regressed against the coefficients of inbreeding since inbreeding depression is linear with respect to the probability of two genes at any locus being homozygous through ancestry. The component egg viability was important because a reduction in OUT 1, IN 1 and KR 1 in the F₂ resulted from mated females producing no viable eggs. Duplicate treatments OUT 2, IN 2 and KR 2 were set up to confirm whether this was a general F₂ phenomenon. Assessment of the fitness components prevented a direct evaluation of the numbers of offspring produced. However a hypothetical estimate of population size and growth rate was made using the percentage survival calculated from life-table analysis. Although not statistically demonstrable in the component analysis, life table analysis indicated that egg viability suffered an inbreeding depression and affected population fitness. It was also evident that treatments OUT 1 and 2 were fitter than treatments IN 1 and 2 and KR 1 and 2 with respect to population fitness. Thus, inbreeding, resulting from sibmating and introduction of a small number of individuals to a laboratorYJ caused a decrease in numbers of offspring produced and population growth rate. This is important in relation to the demise of the cactophagous Lepidoptera and to future biological control programmes.
Keywords: Pyralidae -- South Africa; Cactus -- South Africa; Moths -- South Africa; Insect pests -- Biological control -- South Africa; Inbreeding